2013
DOI: 10.1371/journal.pone.0074458
|View full text |Cite
|
Sign up to set email alerts
|

Status Epilepticus Induces Vasogenic Edema via Tumor Necrosis Factor-α/ Endothelin-1-Mediated Two Different Pathways

Abstract: Status epilepticus (SE) induces vasogenic edema in the piriform cortex with disruptions of the blood-brain barrier (BBB). However, the mechanisms of vasogenic edema formation following SE are still unknown. Here we investigated the endothelin B (ETB) receptor-mediated pathway of SE-induced vasogenic edema. Following SE, the release of tumor necrosis factor-α (TNF-α) stimulated endothelin-1 (ET-1) release and expression in neurons and endothelial cells. In addition, TNF-α-induced ET-1 increased BBB permeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 46 publications
11
61
0
Order By: Relevance
“…5). Consistent with our previous study (Kim et al, 2013), Cav-1 peptide did not affect eNOS expression in endothelial cells following SE (data not shown). Furthermore, the volume of vasogenic edema was 4.8 mm 3 in the PC of vehicle-pretreated animals at 3 days after SE.…”
Section: 4supporting
confidence: 93%
See 1 more Smart Citation
“…5). Consistent with our previous study (Kim et al, 2013), Cav-1 peptide did not affect eNOS expression in endothelial cells following SE (data not shown). Furthermore, the volume of vasogenic edema was 4.8 mm 3 in the PC of vehicle-pretreated animals at 3 days after SE.…”
Section: 4supporting
confidence: 93%
“…Leakage of serum-derived components into the brain parenchyma results in neuronal hyperexcitability and seizure onset ( Therefore, dysfunction of the BBB leads to epileptogenesis and contributes to progression of epilepsy (Nitsch et al, 1985;Cornford and Oldendorf, 1986;Deli et al, 2005;Sztriha et al, 1986;Seiffert et al, 2004). Recently, we have reported that SE triggers a signaling cascade leading to NO production derived from eNOS in endothelial cells (Kim et al, 2013). Since the increased NO synthesis affects BBB permeability in various pathophysiological conditions (Sharma et al, 2000;Wu and Tsirka, 2009) we suggested that eNOS may involve BBB disruption following SE (Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports in the literature showing that SE can cause brain edema that can by itself, contribute to the epileptogenic process [63][64][65], although the mechanisms underlying this process are unknown. Edema resulting from seizures in human or experimental model can be of two types, cytotoxic edema and vasogenic edema [63][64][65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Edema resulting from seizures in human or experimental model can be of two types, cytotoxic edema and vasogenic edema [63][64][65][66][67][68][69]. In the cytotoxic edema, the glutamate hyperstimulation causes intracellular Ca 2+ increase and promotes cytotoxicity in neurons and glial cells [64,70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation